The Growth of Islamic Insurance in Indonesia - Helmi Naufal Satrianto; Muhamad Adifio Bahi; Muhammad Dike Al Ariq; Raffi Farisy (Journal of Islamic Business and Economic Review, 2021)
Along with the increasing Islamic financial market, Islamic insurance has also grown significantly over the years. Hence, this paper wants to examine the reasons, prospects, challenges, and possible strategies of Islamic insurance's development in Indonesia. This study used a qualitative research method proved by data and analysis of previous research. The results show that Indonesia's Muslim population, Islamic banking development, and some regulations backing it up are significant in this increase. This increase is also predicted to persist over the next few years. However, it faced a few challenges, like market competition with conventional insurance that is more popular. Still, this thing is easily overcome by more socialization and promoting Islamic insurance to the public.